Dawn of a New Age Fissure Sealant? A Study Evaluating the Clinical Performance of Embrace WetBond and ART Sealants: Results from a Randomized Controlled Clinical Trial - Haricharan, Praveen Bhoopathi (Eur J Dent, 2019)
Objectives  The main purpose of this article is to evaluate the clinical performance of atraumatic restorative treatment (ART) sealant versus Embrace WetBond sealant in terms of retention and fissure caries prevention among a section of school children in the southern Indian state of Karnataka (ClinicalTrials.gov NCT02716558). Materials and Methods  After obtaining consent from the parents and screening the children against the inclusion cum exclusion criteria, 90 school children whose mandibular first molars were caries free and with a well-defined pit and fissure system were recruited for this spilt mouth trial. The respective molars were allocated either to the ART sealant or the embrace group after the randomization process. The sealants were applied according to the manufacturer’s instructions and followed up at the end of 3rd, 6th, and 12th month, respectively. The outcome measures assessed were the retention and the caries preventive effects of the materials. Results  At the end of the 6th month, about one-fourth of the sealants in either group remained totally intact, without evidence of caries. No significant differences were seen between the sealants either in terms of retention or caries preventive benefits at the end of 12 months. Statistical Analysis  The chi-squared test was used to check differences in proportions. The significance value was set at <0.05. Kappa test was performed to assess the intraexaminer reproducibility with respect to retention and caries status. Conclusion  The moisture-tolerant resin sealant could not replicate the physical properties usually associated with conventional resin sealants. The usage of ART sealants was deemed to be less cumbersome in an outreach setting as observed in this trial.